Negociação coletiva na função pública: abordagem crítica do modelo brasileiro a partir do paradigma espanhol - Paes, Arnaldo Boson (2013)
This research addresses the issue of collective bargaining in the public sector, and it has a critical approach of the Brazilian model from the Spanish paradigm. Thus, the aim is to examine the points of convergence and divergence between the two experiences, considering the need of implementing in Brazil of a democratic system of collective labor relations in the legal and administrative systems. With this perspective, the study is divided in three parts; the first one has as its purpose to analyze the theoretical and normative frameworks which are necessary in order to recognize the right to collective bargaining in the public service. In this first part we also examine the nature of the bond established in the legal and administrative regime and the regulatory tools of the ILO intended to regulate the participation of public servant in determining working conditions in the public service. The second part analyzes the Brazilian model with no collective bargaining, from the examination of the normative constitutional apparatus of the legislation which established the legal-administrative regime, also from the paradigmatic precedent on the subject of the Supreme Court, and also from the case law that subsequently consolidated itself in relation to the collective rights of employees and the Brazilian ratification of the 151st Convention 151 ILO. The third part analyzes the Spanish system of collective bargaining, with emphasis on examining the legal and constitutional model that gradually consolidated itself, assessing in more detail the question of the effectiveness of the legal tools which result from collective bargaining and the role of the courts to guarantee the full and effective exercise of the collective rights for public employees. Throughout the thesis, we analyzed the similarities of the normative and of the jurisprudential contours surrounding the issue in both countries, and we did so as we tried to demonstrate the importance of making good use of the learning process and of the progress observed in Spanish law to conform in and implement in Brazil a system of collective bargaining in the public sector which is consistent with constitutional recognition of collective rights of public servants and the proclamation of a democratic state